Solar chimney power plant generating technology - Ming, Tingzhen (Academic Press, an imprint of Elsevier, 2016)
Solar Chimney Power Plant Generating Technology presents the latest advanced solar chimney power generating technologies to help engineers acquire a comprehensive understanding of the fundamental theories, technologies, and applications of solar chimney power generating systems. The book includes comprehensive theories, very detailed technologies, and many well-illustrated, basic configurations of different types of systems, enabling readers to understand the fundamental theory, the design methods of solar chimney systems, and the basic parameters of the construction and operation of these systems.